Polarizing plate with adhesive layer

The polarizing plate with a moisture-permeable adhesive layer and cyclic polyolefin resin protective film addresses iodine loss and curling issues, ensuring stability in harsh environments.

JP7599853B2Active Publication Date: 2024-12-16SUMITOMO CHEM CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2020115807
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-03
Publication Date
2024-12-16
Estimated Expiration
2040-07-03

AI Technical Summary

Technical Problem

Existing polarizing plates experience iodine loss and curling issues in high temperature and high humidity environments, particularly when protective films are laminated on one side via an adhesive layer.

Method used

The polarizing plate is designed with a specific moisture permeability range (180-1500 g/(m²·day) for the adhesive layer and includes a protective film made of cyclic polyolefin resin, along with a functional layer that suppresses iodine loss and facilitates quick curl elimination.

Benefits of technology

The design effectively prevents iodine loss and reduces curling time in high temperature and high humidity conditions, maintaining the integrity of the polarizing plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599853000003
    Figure 0007599853000003
  • Figure 0007599853000004
    Figure 0007599853000004
  • Figure 0007599853000005
    Figure 0007599853000005
Patent Text Reader

Abstract

To provide a polarizing plate with an adhesive layer, which minimizes iodine elution even in high-temperature / high-humidity environments and allows a generated curl to be easily eliminated.SOLUTION: A polarizing plate 100 with an adhesive layer is provided, comprising a polarizer 10, a protective film 11 provided on one side of the polarizer via an adhesive layer 12, a first adhesive layer 13 provided on the other side of the polarizer. The polarizer is a hydrophilic polymer film with iodine absorbed therein. The first adhesive layer exhibits a moisture permeability of 180 g / (m2 / day) to 1500 g / (m2 / day) at a temperature of 40°C and relative humidity of 90% RH.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate with a pressure-sensitive adhesive layer, and further to an image display device including the same. [Background technology]

[0002] Patent Document 1 proposes a polarizing plate with a pressure-sensitive adhesive layer, in which a polarizer protective film is laminated on one side of a polarizer via an adhesive layer, and a pressure-sensitive adhesive layer is laminated on the other side. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-247574 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a polarizing plate with a pressure-sensitive adhesive layer in which iodine loss is suppressed even in a high-temperature and high-humidity environment and curling is easily eliminated. [Means for solving the problem]

[0005] The present invention provides the following pressure-sensitive adhesive layer-attached polarizing plate and image display device. [1] A polarizing plate with a pressure-sensitive adhesive layer, comprising a polarizer, a protective film disposed on one side of the polarizer via an adhesive layer, and a first pressure-sensitive adhesive layer disposed on the other side of the polarizer, the polarizer is a hydrophilic polymer film having iodine adsorbed thereon; The first pressure-sensitive adhesive layer has a moisture permeability of 180 g / (m 2 ·day) or more 1500g / (m 2 1. A polarizing plate with an adhesive layer, the temperature of which is 100° C. or less. [2] The polarizing plate with a pressure-sensitive adhesive layer according to [1], wherein the first pressure-sensitive adhesive layer is a layer made of a pressure-sensitive adhesive containing a (meth)acrylic resin. [3] The polarizing plate with a pressure-sensitive adhesive layer according to [1] or [2], wherein the first pressure-sensitive adhesive layer has a thickness of 10 μm or more. [4] The polarizing plate with a pressure-sensitive adhesive layer according to any one of [1] to [3], wherein the protective film is a film made of a cyclic polyolefin resin. [5] A laminate for a flexible image display device, comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of [1] to [4], and a front panel or a touch sensor. [6] An image display device comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of [1] to [4]. [7] A polarizing plate with a pressure-sensitive adhesive layer, comprising: a polarizer; a protective film disposed on one side of the polarizer via an adhesive layer; and a second pressure-sensitive adhesive layer, a functional layer, and a first pressure-sensitive adhesive layer, in this order, from the polarizer side, on the other side of the polarizer, The functional layer is a single layer of a cured liquid crystal layer alone, or a multilayer of two or more layers selected from the group consisting of a cured liquid crystal layer, an alignment layer, and an attachment layer; the polarizer is a hydrophilic polymer film having iodine adsorbed thereon; The moisture permeability of a laminate composed of the second pressure-sensitive adhesive layer, the functional layer, and the first pressure-sensitive adhesive layer at a temperature of 40° C. and a relative humidity of 90% RH is 180 g / (m 2 ·day) or more 1500g / (m 2 1. A polarizing plate with an adhesive layer, the temperature of which is 100° C. or less. [8] The polarizing plate with a pressure-sensitive adhesive layer according to [7], wherein the protective film is a film made of a cyclic polyolefin resin. [9] The polarizing plate with a pressure-sensitive adhesive layer according to [7] or [8], wherein the functional layer includes a first cured liquid crystal layer and a second cured liquid crystal layer.

[10] A laminate for a flexible image display device, comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of [7] to [9], and a front panel or a touch sensor.

[11] An image display device comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of [7] to [9]. Effect of the Invention

[0006] According to the present invention, it is possible to provide a polarizing plate with a pressure-sensitive adhesive layer in which iodine loss is suppressed even in a high-temperature and high-humidity environment and curling is easily prevented. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view showing an example of a pressure-sensitive adhesive layer-attached polarizing plate of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of the pressure-sensitive adhesive layer-attached polarizing plate of the present invention. [Diagram 3] FIG. 2 is a schematic diagram showing a method for installing a sample for evaluating iodine loss. [Figure 4] 1 is a diagram showing an image of the polarizing plate with a pressure-sensitive adhesive layer obtained in Example 1, observed under an optical microscope. [Diagram 5] FIG. 2 is a diagram showing an example of data obtained by converting an observed image of the polarizing plate with a pressure-sensitive adhesive layer obtained in Example 1 into black and white with 256 gradations. [Figure 6] FIG. 4 is a schematic diagram showing a method for measuring curl height. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention will be described with reference to the drawings, but the present invention is not limited to the following embodiment. In all of the drawings, the scale of each component is appropriately adjusted to make it easier to understand, and the scale of each component shown in the drawings does not necessarily match the scale of the actual component.

[0009] <Polarizing plate with adhesive layer> [First embodiment] A polarizing plate with an adhesive layer according to a first embodiment of the present invention (hereinafter also referred to as a first polarizing plate) comprises a polarizer, a protective film arranged on one side of the polarizer via an adhesive layer, and a first adhesive layer arranged on the other side of the polarizer. An example of the layer structure of the first polarizing plate is shown in Fig. 1. The first polarizing plate 100 shown in Fig. 1 comprises a protective film 11, an adhesive layer 12, a polarizer 10, and a first adhesive layer 13, in this order.

[0010] The first polarizing plate 100 is preferably composed of only a protective film 11, an adhesive layer 12, a polarizer 10, and a first pressure-sensitive adhesive layer 13. In the first polarizing plate 100, the protective film 11 is preferably laminated on one surface of the polarizer 10 via only the adhesive layer 12. In the first polarizing plate 100, the first pressure-sensitive adhesive layer 13 is preferably laminated directly on the surface of the polarizer 10 opposite to the adhesive layer 12 side. When the first polarizing plate 100 is composed of only the protective film 11, the adhesive layer 12, the polarizer 10, and the first pressure-sensitive adhesive layer 13, the first polarizing plate 100 can be used as a linear polarizing plate with a pressure-sensitive adhesive layer.

[0011] The thickness of the first polarizing plate 100 is not particularly limited since it varies depending on the function required of the first polarizing plate 100 and the use of the first polarizing plate 100, and may be, for example, 5 μm or more, or 10 μm or more, or may be, for example, 200 μm or less, and may be 150 μm or less, 120 μm or less, 100 μm or less, 80 μm or less, 70 μm or less, or may be, for example, 200 μm or less. m It may be the following.

[0012] [Polarizer] Polarizer 10 has the property of absorbing linearly polarized light having a vibration plane parallel to its absorption axis and transmitting linearly polarized light having a vibration plane perpendicular to the absorption axis (parallel to the transmission axis). Polarizer 10 is a film in which iodine is adsorbed onto a hydrophilic polymer film. Polarizer 10 can be manufactured, for example, through a process of uniaxially stretching a hydrophilic polymer film, a process of dyeing the hydrophilic polymer film with iodine to adsorb the iodine, a process of treating the hydrophilic polymer film with the iodine adsorbed thereon with an aqueous solution of boric acid, and a process of washing with water after the treatment with the aqueous solution of boric acid.

[0013] Examples of hydrophilic polymer films include polyvinyl alcohol resin films. Polyvinyl alcohol resins are obtained by saponifying polyvinyl acetate resins. Examples of polyvinyl acetate resins include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate and other monomers copolymerizable therewith. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acid compounds, olefin compounds, vinyl ether compounds, unsaturated sulfone compounds, and (meth)acrylamide compounds having an ammonium group. In this specification, "(meth)acrylic" means at least one selected from acrylic and methacrylic. The same applies to "(meth)acrylate" and the like.

[0014] The degree of saponification of the polyvinyl alcohol resin is usually about 85 mol% or more and 100 mol% or less, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and polyvinyl formal, polyvinyl acetal, etc. modified with aldehydes can also be used. The degree of polymerization of the polyvinyl alcohol resin is usually 1000 or more and 10000 or less, preferably 1500 or more and 5000 or less.

[0015] The polarizer 10 has iodine adsorbed and oriented, and the boron content is 5.5 mass% or less, preferably 5.0 mass% or less, and more preferably 4.5 mass% or less, so that shrinkage caused by heating can be suppressed. The boron content is preferably 0.5 mass% or more, more preferably 1 mass% or more, and may be 2 mass% or more. By having a boron content of 0.5 mass% or more, it is possible to stably retain iodine and suppress discoloration.

[0016] The thickness of the polarizer 10 is usually 30 μm or less, preferably 15 μm or less, more preferably 13 μm or less, further preferably 10 μm or less, and particularly preferably 8 μm or less. The thickness of the polarizer 10 is usually 2 μm or more, preferably 3 μm or more, and may be, for example, 5 μm or more.

[0017] [Protective film] The protective film 11 is disposed on one side of the polarizer 10 and can have the function of protecting the polarizer 10. The protective film 11 can be a coating layer or a film made of an optically transparent thermoplastic resin, for example, a cyclic polyolefin-based resin; a cellulose acetate-based resin made of a resin such as triacetyl cellulose or diacetyl cellulose; a polyester-based resin made of a resin such as polyethylene terephthalate, polyethylene naphthalate, or polybutylene terephthalate; a polycarbonate-based resin; a (meth)acrylic-based resin; a polypropylene-based resin, or a mixture of one or more of these.

[0018] A hard coat layer may be formed on the protective film 11. The hard coat layer may be formed on one side of the protective film 11 or on both sides. By providing the hard coat layer, the protective film 11 can be improved in hardness and scratch resistance. The hard coat layer may be a cured layer of, for example, an acrylic resin, a silicone resin, a polyester resin, a urethane resin, an amide resin, an epoxy resin, or the like. The hard coat layer may contain an additive to improve strength. The additive is not limited, and examples thereof include inorganic fine particles, organic fine particles, or a mixture thereof. The hard coat layer is, for example, a cured layer of an ultraviolet curing resin. Examples of the ultraviolet curing resin include an acrylic resin, a silicone resin, a polyester resin, a urethane resin, an amide resin, and an epoxy resin.

[0019] The thickness of the protective film 11 is usually 1 μm or more and 100 μm or less, and from the standpoint of strength, handleability, etc., it is preferably 5 μm or more and 80 μm or less, more preferably 8 μm or more and 60 μm or less, even more preferably 12 μm or more and 45 μm or less, and may be 30 μm or less.

[0020] [Adhesive layer] The adhesive layer 12 can be interposed between the protective film 11 and the polarizer 10 to bond them together. Examples of the adhesive forming the adhesive layer 12 include a water-based adhesive, an active energy ray-curable adhesive, and a thermosetting adhesive, and it is preferable to use a water-based adhesive or an active energy ray-curable adhesive. The surfaces of the protective film 11 and the polarizer 10 facing each other to be bonded together via the adhesive layer 12 may be previously subjected to a corona treatment, a plasma treatment, a flame treatment, or the like, and may have a primer layer or the like.

[0021] The thickness of the adhesive layer 12 is from 0.01 μm to 10 μm in order to ensure bonding properties.

[0022] [First adhesive layer] In the first embodiment, the first pressure-sensitive adhesive layer 13 has a moisture permeability (hereinafter, simply referred to as "moisture permeability") of 180 g / (m 2 ·day) or more 1500g / (m 2 ·day) or less. The moisture permeability is measured according to the measurement method described in the Examples section below.

[0023] The polarizing plate with an adhesive layer is attached to an organic EL display element or a liquid crystal cell (usually an inorganic glass surface) via the adhesive layer. When the polarizer is a hydrophilic resin film, it tends to have poor moist heat resistance after being attached to an inorganic glass surface, and iodine tends to escape from the end of the polarizer, i.e., so-called iodine escape tends to occur easily. In particular, iodine escape tends to occur easily in a polarizing plate with an adhesive layer in which a protective film is placed on one side of the polarizer via only an adhesive layer and an adhesive layer is placed directly on the other side. The first polarizing plate 100 has a moisture permeability of the first adhesive layer 13 of 1500 g / (m2 ·day), iodine loss tends to be easily suppressed. When protective films are laminated on both sides of the polarizer via adhesive layers (double-sided protected polarizing plate), such iodine loss tends to be less likely to occur.

[0024] Furthermore, the protective film provided in a polarizing plate with an adhesive layer is usually more rigid than the adhesive layer. Therefore, when a polarizing plate with an adhesive layer is manufactured by laminating a protective film to one side of a polarizer via only an adhesive layer and laminating an adhesive layer directly to the other side, the polarizing plate with an adhesive layer manufactured in this manner tends to curl more easily than a polarizing plate having protective films on both sides. The curl can be eliminated by storing the polarizing plate in an atmosphere different from that in the lamination process, for example, at room temperature and high humidity, but it is desirable that the time required to eliminate the curl is short. The first polarizing plate 100 has a moisture permeability of the first adhesive layer 13 of 180 g / (m 2 By keeping the drying time at 10-20 days or more, the curls tend to be removed in a relatively short period of time.

[0025] The moisture permeability of the first adhesive layer 13 is preferably 300 g / (m 2 ) from the viewpoints of suppressing iodine loss and shortening the time required for curl elimination. 2 ·day) or more 1400g / (m 2 ·day) or less, and more preferably 500g / (m 2 ·day) or more 1300g / (m 2 ·day) or less, and more preferably 700 g / (m 2 ·day) or more 1200g / (m 2 ·day) or less.

[0026] The moisture permeability of the first adhesive layer 13 can be adjusted, for example, by selecting the type and ratio of the components of the adhesive composition, the crosslinking density, etc. Alternatively, it can be adjusted by laminating a plurality of adhesives with different moisture permeabilities. The crosslinking density can be adjusted by changing the manufacturing conditions or by appropriately selecting the type and amount of the crosslinking agent. The moisture permeability can be adjusted by laminating adhesives, for example, by appropriately determining the thickness ratio of the low moisture permeable adhesive layer and the high moisture permeable adhesive. Examples of low moisture permeable adhesives used for lamination include adhesives mainly composed of rubber-based resins, and many acrylic adhesives used for optical applications have relatively high moisture permeability.

[0027] The first adhesive layer 13 can be composed of one or more layers of an adhesive composition mainly composed of a resin such as a (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether resin. Among them, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is suitable and preferably contained. The adhesive composition may be of an active energy ray curing type or a heat curing type.

[0028] As the (meth)acrylic resin (base polymer) used in the pressure-sensitive adhesive composition, for example, a polymer or copolymer containing one or more (meth)acrylic acid esters as monomers, such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, is preferably used. It is preferable to copolymerize a polar monomer into the base polymer. Examples of the polar monomer include monomers having a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, and the like, such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate.

[0029] The adhesive composition may contain only the base polymer, but usually further contains a crosslinking agent. Examples of the crosslinking agent include divalent or higher metal ions that form a carboxylate metal salt with a carboxyl group; polyamine compounds that form an amide bond with a carboxyl group; polyepoxy compounds or polyols that form an ester bond with a carboxyl group; and polyisocyanate compounds that form an amide bond with a carboxyl group. Among them, polyisocyanate compounds are preferred.

[0030] The pressure-sensitive adhesive composition may contain, as other components, one or more additives such as antistatic agents, solvents, crosslinking catalysts, tackifiers, plasticizers, softeners, pigments, rust inhibitors, inorganic fillers, and organic fillers.

[0031] The thickness of the first pressure-sensitive adhesive layer 13 may be, for example, 3 μm or more, preferably 5 μm or more, and more preferably 10 μm or more. The thickness of the first pressure-sensitive adhesive layer 13 may be, for example, 50 μm or less, preferably 40 μm or less, and more preferably 30 μm or less, and from the viewpoint of thinning, it is further preferably 27 μm or less.

[0032] [Other layers] The first polarizing plate 100 may include, as other layers, a protective film for protecting the surface (such as the surface of the protective film 11) and a separator film (hereinafter also referred to as a separator) laminated on the outer surface of the first adhesive layer 13.

[0033] [Protection film] For example, after a polarizing plate is attached to an image display element or other optical member, the protective film is peeled off and removed together with the adhesive layer that the protective film has.

[0034] The protective film is, for example, composed of a base film and an adhesive layer laminated thereon. The adhesive layer is as described above. The resin constituting the base film may be, for example, a thermoplastic resin such as a polyethylene-based resin such as polyethylene, a polypropylene-based resin such as polypropylene, a polyester-based resin such as polyethylene terephthalate or polyethylene naphthalate, or a polycarbonate-based resin. A polyester-based resin such as polyethylene terephthalate is preferred.

[0035] [Separate film] The separate film may be a film made of a polyethylene-based resin such as polyethylene, a polypropylene-based resin such as polypropylene, a polyester-based resin such as polyethylene terephthalate, or the like. Among them, a stretched film of polyethylene terephthalate is preferable. The separate film may have a release treatment applied to its surface.

[0036] [Second embodiment] A polarizing plate with an adhesive layer according to a second embodiment of the present invention (hereinafter also referred to as a second polarizing plate) comprises a polarizer and a protective film disposed on one side of the polarizer via an adhesive layer, and comprises, from the polarizer side, a second adhesive layer, a functional layer, and a first adhesive layer in this order on the other side of the polarizer. An example of the layer structure of the second polarizing plate is shown in FIG. 2. FIG. 2 is a schematic cross-sectional view of an example of the second polarizing plate. The second polarizing plate 200 shown in FIG. 2 comprises, in this order, a protective film 11, an adhesive layer 12, a polarizer 10, a second adhesive layer 14, a functional layer 15, and a first adhesive layer 13.

[0037] The second polarizing plate 200 is preferably composed of only a protective film 11, an adhesive layer 12, a polarizer 10, a second pressure-sensitive adhesive layer 14, a functional layer 15, and a first pressure-sensitive adhesive layer 13. In the second polarizing plate 200, the protective film 11 is preferably laminated on one side of the polarizer 10 via only the adhesive layer 12. In the second polarizing plate 200, the second pressure-sensitive adhesive layer 14 is preferably laminated directly on the surface of the polarizer 10 opposite to the adhesive layer 12 side.

[0038] The same descriptions as for the protective film 11, adhesive layer 12, first pressure-sensitive adhesive layer 13, and polarizer 10 in the first polarizer 100 above are applied to the protective film 11, adhesive layer 12, and polarizer 10 in the second polarizer 200. In addition, the second polarizer 200 may include other layers such as a protective film and a separate film described in the first polarizer 100 above.

[0039] [First adhesive layer and second adhesive layer] The first adhesive layer 13 can have a function of bonding the second polarizing plate 200 to an image display device. The second adhesive layer 14 can be interposed between the polarizer 10 and the functional layer 15 to bond them together. The first adhesive layer 13 and the second adhesive layer 14 may be composed of an adhesive composition mainly composed of a resin such as a (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether resin. The adhesive composition forming the first adhesive layer 13 (hereinafter also referred to as the "first adhesive composition") and the adhesive composition forming the second adhesive layer 14 (hereinafter also referred to as the "second adhesive composition") may be the same or different. As the first and second adhesive compositions, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is suitable. The first and second adhesive compositions may be active energy ray curable or heat curable.

[0040] The descriptions of the (meth)acrylic resin (base polymer), crosslinking agent and other components used in the first and second adhesive compositions in the second polarizing plate 200 are the same as those of the (meth)acrylic resin (base polymer), crosslinking agent and other components described above for the first polarizing plate 100.

[0041] The moisture permeability of the first adhesive layer 13 is, for example, 10 g / (m 2 ·day) or more, and preferably 20 g / (m 2 ·day) or more than 6000g / (m 2 ·day) or less, more preferably 100g / (m 2 ·day) or more 3000g / (m 2·day) or less, and more preferably 180 g / (m 2 ·day) or more 1500g / (m 2 ·day) or less.

[0042] The thickness of the first pressure-sensitive adhesive layer 13 may be, for example, 3 μm or more, preferably 5 μm or more, and more preferably 10 μm or more. For example, it may be 50 μm or less, preferably 40 μm or less, and more preferably 30 μm or less, and from the viewpoint of thinning, it is further preferably 27 μm or less.

[0043] The thickness of the second pressure-sensitive adhesive layer 14 may be, for example, 2 μm or more and 30 μm or less, and preferably 3 μm or more and 20 μm or less. For example, it may be 10 μm or more, but from the viewpoint of further reducing the thickness, it is preferably 15 μm or less, more preferably 10 μm or less, and particularly preferably 7 μm or less.

[0044] [Functional Layer] The functional layer 15 is a single layer of a cured liquid crystal layer alone, or a multilayer of two or more layers selected from the group consisting of a cured liquid crystal layer, an alignment layer, and an attachment layer. The functional layer 15 preferably includes two cured liquid crystal layers, and more preferably includes a layer structure in which two cured liquid crystal layers are laminated via an attachment layer.

[0045] [Liquid crystal hardening layer] The liquid crystal cured layer may be a retardation layer made of a cured product of a polymerizable liquid crystal compound, which is formed by applying and aligning a polymerizable liquid crystal compound on a substrate to exhibit optical anisotropy. Examples of the retardation layer made of a cured product of a polymerizable liquid crystal compound include the first to fifth forms. First form: A retardation layer in which rod-shaped liquid crystal compounds are aligned horizontally to the supporting substrate Second type: A retardation layer in which rod-shaped liquid crystal compounds are aligned perpendicular to the substrate Third form: A retardation layer in which the direction of the rod-shaped liquid crystal molecules changes in a helical manner in the plane. Fourth form: Retardation layer in which discotic liquid crystal compounds are tilted Fifth form: A biaxial retardation layer in which discotic liquid crystal compounds are aligned perpendicular to the substrate For example, as an optical film used in an organic electroluminescence display, the first, second, or fifth embodiment is preferably used. Alternatively, retardation layers of these embodiments may be laminated and used.

[0046] When the retardation layer is a layer made of a polymer in an oriented state of a polymerizable liquid crystal compound (hereinafter, sometimes referred to as an "optically anisotropic layer"), the retardation layer preferably has reverse wavelength dispersion. Reverse wavelength dispersion is an optical property in which the liquid crystal alignment in-plane retardation value at a short wavelength is smaller than the liquid crystal alignment in-plane retardation value at a long wavelength, and preferably, the retardation film satisfies the following formulas (1) and (2). Here, Re(λ) represents the in-plane retardation value for light with a wavelength of λ nm. Re(450) / Re(550)≦1 (1) 1≦Re(630) / Re(550) (2) When the retardation layer is in the first form and has reverse wavelength dispersion, coloring during black display in a display device is reduced, which is preferable, and in the formula (1), 0.82≦Re(450) / Re(550)≦0.93 is more preferable. Further, 120≦Re(550)≦150 is more preferable.

[0047] Examples of the polymerizable liquid crystal compound used in the formation of the retardation layer include compounds having a polymerizable group among the compounds described in "3.8.6 Network (completely crosslinked type)" and "6.5.1 Liquid crystal material b. Polymerizable nematic liquid crystal material" in Liquid Crystal Handbook (edited by Liquid Crystal Handbook Editorial Committee, published by Maruzen Co., Ltd. on October 30, 2000), as well as the polymerizable liquid crystal compounds described in JP 2010-31223 A, JP 2010-270108 A, JP 2011-6360 A, JP 2011-207765 A, JP 2011-162678 A, JP 2016-81035 A, International Publication No. 2017 / 043438 A and JP 2011-207765 A. Examples of a method for producing a retardation layer from a polymer in an aligned state of a polymerizable liquid crystal compound include the method described in JP-A-2010-31223.

[0048] The thickness of the retardation layer, which is a liquid crystal cured layer obtained by curing a polymerizable liquid crystal compound, is, for example, 0.1 μm to 10 μm, preferably 0.5 μm to 8 μm, and more preferably 1 μm to 6 μm.

[0049] The retardation layer can be a λ / 4 retardation layer that imparts a retardation of 1 / 4 wavelength to transmitted light, a λ / 2 retardation layer that imparts a retardation of 1 / 2 wavelength to transmitted light, a positive A plate, or a positive C plate. The functional layer can include two liquid crystal hardened layers. When the functional layer includes a first liquid crystal hardened layer and a second liquid crystal hardened layer, the combination of the liquid crystal hardened layers can be a combination of a λ / 2 retardation layer and a λ / 4 retardation layer, a combination of a λ / 4 retardation layer and a positive C layer, etc.

[0050] The second polarizer 200 may be configured as a circular polarizer having a λ / 4 retardation layer. The circular polarizer can be used as an anti-reflection polarizer.

[0051] [Alignment layer] The alignment layer can be disposed between the substrate and the layer of the cured polymerizable liquid crystal compound. The alignment layer has an alignment regulating force that causes the liquid crystal cured layer formed thereon to be aligned in a desired direction. Examples of the alignment layer include an alignment polymer layer formed from an alignment polymer, a photoalignment polymer layer formed from a photoalignment polymer, and a groove alignment film having a concave-convex pattern or a plurality of grooves on the layer surface. The thickness of the alignment layer may be, for example, 10 nm or more and 500 nm or less, and is preferably 10 nm or more and 200 nm or less.

[0052] The oriented polymer layer can be formed by applying a composition in which an oriented polymer is dissolved in a solvent to a substrate, removing the solvent, and performing a rubbing treatment as necessary. In this case, the orientation control force of the oriented polymer layer formed of the oriented polymer can be arbitrarily adjusted by the surface state of the oriented polymer and the rubbing conditions.

[0053] The photo-alignable polymer layer can be formed by applying a composition containing a polymer or monomer having a photoreactive group and a solvent to a substrate layer, and irradiating the composition with polarized light. In this case, the alignment control force of the photo-alignable polymer layer can be arbitrarily adjusted by the conditions of irradiating the photo-alignable polymer with polarized light, etc.

[0054] The groove alignment film can be formed, for example, by a method of forming a concave-convex pattern by exposing the surface of a photosensitive polyimide film through an exposure mask having slits in a pattern shape, developing, etc., a method of forming an uncured layer of active energy ray curable resin on a plate-shaped master having grooves on its surface, transferring this layer to a substrate, and curing the layer, or a method of forming an uncured layer of active energy ray curable resin on a substrate, and pressing a roll-shaped master having concave-convex shapes against this layer to form concave-convex shapes and then curing the layer.

[0055] [Lamination layer] The bonding layer can be arranged to bond the two layers. The bonding layer can be made of an adhesive or a pressure sensitive adhesive. When the functional layer 15 includes two layers of cured liquid crystal layers, the two layers of cured liquid crystal layers can be bonded by the bonding layer.

[0056] The adhesive layer may be made of a water-based adhesive, an active energy ray curable adhesive, a thermosetting adhesive, etc. The thickness of the adhesive layer is from 0.01 μm to 10 μm in order to ensure bonding properties.

[0057] The adhesive may be composed of the same adhesive composition as the adhesive composition forming the first and second adhesive layers, or may be composed of an adhesive composition mainly composed of a resin such as a (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether resin (hereinafter also referred to as the "third adhesive composition"). As the third adhesive composition, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is suitable. The third adhesive composition may be an active energy ray curable type or a heat curable type. The thickness of the adhesive layer is usually 0.1 μm or more and 150 μm or less, for example, 3 μm or more and 60 μm or less, and from the viewpoint of thinning, it is preferably 30 μm or less, and more preferably 20 μm or less. The thickness of the adhesive layer may be, for example, 10 μm or more, but from the viewpoint of further thinning, it is 15 μm or less, preferably 10 μm or less, and particularly preferably 7 μm or less.

[0058] [Moisture permeability] The second polarizing plate 200 has a laminate composed of the second adhesive layer 14, the functional layer 15, and the first adhesive layer 13, and has a moisture permeability of 180 g / (m 2 ·day) or more 1500g / (m 2 ·day) or less.

[0059] A polarizing plate with an adhesive layer, in which a protective film is laminated on one side of a polarizer via only an adhesive layer, and a second adhesive layer, a functional layer, and a first adhesive layer are laminated directly on the other side in this order from the polarizer side, tends to have poor moist heat resistance after being attached to an inorganic glass surface even though it has the second adhesive layer and the functional layer, and therefore iodine tends to escape from the edge of the polarizer, which is known as iodine loss. 200 The moisture permeability of a laminate (hereinafter, for the sake of brevity, simply referred to as the "laminate") composed of the second pressure-sensitive adhesive layer 14, the functional layer 15, and the first pressure-sensitive adhesive layer 13 is 1500 g / (m 2 By keeping the time required for iodine extraction within 10 days, iodine loss tends to be suppressed.

[0060] In addition, although the second polarizing plate 200 has a functional layer, the liquid crystal cured layer and the lamination layer constituting the functional layer are relatively thin. Since the protective film of the second polarizing plate is more rigid than the adhesive layer, even when the second polarizing plate 200 has a functional layer, it tends to curl more easily than a polarizing plate having protective films on both sides. The second polarizing plate 200 has a laminate composed of the second adhesive layer 14, the functional layer 15, and the first adhesive layer 13, and has a moisture permeability of 180 g / (m 2 By keeping the drying time at 10-20 days or more, the curls tend to be removed in a relatively short period of time.

[0061] The moisture permeability of the laminate is preferably 220 g / (m 2 ) from the viewpoints of suppressing iodine loss and shortening the time required for curl elimination. 2 ·day) or more 800g / (m 2 ·day) or less, and more preferably 240g / (m 2 ·day) or more 700g / (m 2 ·day) or less, and more preferably 250 g / (m 2 ·day) or more 600g / (m 2 ·day) or less.

[0062] The moisture permeability of the laminate can be adjusted to within the above range, for example, by adjusting the moisture permeability of first pressure-sensitive adhesive layer 13 and second pressure-sensitive adhesive layer 14.

[0063] [Method of manufacturing a polarizing plate with an adhesive layer] The first polarizing plate 100 can be manufactured, for example, as follows. First, the polarizer 10 and the protective film 11 are laminated via the adhesive layer 12. The polarizing plate may be manufactured by preparing a long member, laminating the respective members by roll-to-roll and then cutting them into a predetermined shape, or by cutting the respective members into a predetermined shape and then laminating them. After laminating the protective film 1 to the polarizer 10, a heating step or a humidity adjustment step may be performed. Then, the first pressure-sensitive adhesive layer 13 formed on a release film is laminated on the polarizer 10.

[0064] The second polarizing plate 200 can be manufactured, for example, as follows. First, the polarizer 10 and the protective film 11 are laminated via the adhesive layer 12. The polarizing plate may be manufactured by preparing long members, bonding the respective members together by roll-to-roll and then cutting them into a predetermined shape, or by cutting the respective members into a predetermined shape and then bonding them together. After bonding the protective film 1 to the polarizer 10, a heating step or a humidity adjustment step may be performed.

[0065] When the functional layer 15 is a retardation layer, it can be manufactured, for example, as follows. An alignment film is formed on a substrate, and a coating liquid containing a polymerizable liquid crystal compound is applied on the alignment film. In a state where the polymerizable liquid crystal compound is aligned, active energy rays are irradiated to harden the polymerizable liquid crystal compound. A first adhesive layer 13 formed on a release film is laminated on the layer of the hardened polymerizable liquid crystal compound. Then, the substrate and / or the alignment film are peeled off. Then, a second adhesive layer 14 formed on a release film is laminated on the polarizer 10. The retardation layer may be manufactured by preparing long members, laminating the respective members by roll-to-roll and then cutting them into a predetermined shape, or by laminating the respective members after cutting them into a predetermined shape.

[0066] Then, the release film laminated on the second adhesive layer 14 is peeled off, and the functional layer 15 and the polarizer 10 are bonded together via the second adhesive layer 14, thereby producing the second polarizing plate 200.

[0067] <Image display device> The first polarizing plate 100 and the second polarizing plate 200 are disposed on the front surface (viewing side) of an image display panel and can be used as components of an image display device. The polarizing plate with an adhesive layer, which is a circular polarizing plate, can also be used as an anti-reflection polarizing plate that imparts an anti-reflection function to an image display device. The image display device is not particularly limited, and examples thereof include image display devices such as organic electroluminescence (organic EL) display devices, inorganic electroluminescence (inorganic EL) display devices, liquid crystal display devices, and electroluminescence display devices.

[0068] [Flexible image display device] The image display device may be a flexible image display device. The flexible image display device includes a laminate for a flexible image display device, which will be described later, and an organic EL display panel, and is configured to be bendable, with the laminate for a flexible image display device being disposed on the viewing side of the organic EL display panel.

[0069] <Laminate for flexible image display devices> The laminate for flexible image display device includes the polarizing plate with the adhesive layer of the present invention, and a front plate or a touch sensor. The laminate order of the polarizing plate with the adhesive layer of the present invention, the front plate, and the touch sensor may be, for example, from the viewing side, the front plate, the polarizing plate with the adhesive layer of the present invention, and the touch sensor. The laminate order is preferably the front plate, the touch sensor, and the polarizing plate with the adhesive layer of the present invention. If the polarizing plate is present on the viewing side of the touch sensor, the pattern of the touch sensor is less visible, which is preferable because the visibility of the displayed image is improved. Each member can be laminated using an adhesive, an adhesive, or the like. In addition, the laminate for flexible image display device can be provided with a light-shielding pattern formed on at least one surface of any one of the layers of the front plate, the polarizing plate, and the touch sensor.

[0070] [Front plate] A front plate may be disposed on the viewing side of the polarizing plate. The front plate can be laminated to the polarizing plate via an adhesive layer. Examples of the adhesive layer include the above-mentioned pressure-sensitive adhesive layer and adhesive layer.

[0071] Examples of the front plate include glass and resin film having a hard coat layer on at least one side. As the glass, for example, highly transparent glass or reinforced glass can be used. In particular, when a thin transparent surface material is used, chemically reinforced glass is preferable. The thickness of the glass can be, for example, 100 μm to 5 mm.

[0072] A front panel comprising a hard coat layer on at least one side of a resin film can have flexible properties, unlike the rigidity of existing glass. The thickness of the hard coat layer is not particularly limited, and may be, for example, 5 to 100 μm.

[0073] Examples of resin films include cycloolefin derivatives having units of monomers containing cycloolefins such as norbornene or polycyclic norbornene monomers, cellulose (diacetyl cellulose, triacetyl cellulose, acetyl cellulose butyrate, isobutyl ester cellulose, propionyl cellulose, butyryl cellulose, acetylpropionyl cellulose), 、 The resin film may be a film formed of a polymer such as an ethylene-vinyl acetate copolymer, a polycycloolefin, a polyester, a polystyrene, a polyamide, a polyetherimide, a polyacrylic, a polyimide, a polyamideimide, a polyethersulfone, a polysulfone, a polyethylene, a polypropylene, a polymethylpentene, a polyvinyl chloride, a polyvinylidene chloride, a polyvinyl alcohol, a polyvinyl acetal, a polyether ketone, a polyether ether ketone, a polyethersulfone, a polymethyl methacrylate, a polyethylene terephthalate, a polybutylene terephthalate, a polyethylene naphthalate, a polycarbonate, a polyurethane, or an epoxy. The resin film may be an unstretched film, a uniaxially or biaxially stretched film, or a mixture of two or more of these polymers. As the resin film, a polyamideimide film or a polyimide film having excellent transparency and heat resistance, a uniaxially or biaxially stretched polyester film, a cycloolefin derivative film having excellent transparency and heat resistance and capable of handling large-sized films, a polymethyl methacrylate film, and a triacetyl cellulose and an isobutyl ester cellulose film having no transparency and optical anisotropy are preferable. The thickness of the resin film may be from 5 to 200 μm, preferably from 20 to 100 μm.

[0074] [Shading pattern] The light-shielding pattern (bezel) is formed on at least one surface of any of the front plate, the polarizing plate, and the touch sensor constituting the laminate for flexible image display devices. For example, it can be formed on the display element side of the front plate. The light-shielding pattern can hide each wiring of the display device so that it is not visible to the user. The color and material of the light-shielding pattern are not particularly limited, and it can be formed of a resin material having various colors such as black, white, and gold. In one embodiment, the thickness of the light-shielding pattern may be in the range of 2 μm to 50 μm, preferably 4 μm to 30 μm, and more preferably 6 μm to 15 μm. In addition, a shape can be given to the light-shielding pattern in order to suppress the inclusion of air bubbles and the visibility of the boundary due to the step between the light-shielding pattern and the display part.

[0075] [Touch sensor] The touch sensor is used as an input means. Various types of touch sensors have been proposed, such as a resistive film type, a surface acoustic wave type, an infrared type, an electromagnetic induction type, and a capacitance type, and any type may be used. Among them, the capacitance type is preferable. The capacitance type touch sensor is divided into an active area and a non-active area located on the outer periphery of the active area. The active area is an area corresponding to an area (display area) where a screen is displayed on a display panel, and is an area where a touch by a user is sensed, and the non-active area is an area corresponding to an area (non-display area) where a screen is not displayed on a display device. The touch sensor may include a substrate having a flexible characteristic; a sensing pattern formed in the active area of ​​the substrate; and each sensing line formed in the non-active area of ​​the substrate for connecting to an external driving circuit via the sensing pattern and a pad part. The substrate having a flexible characteristic may be made of the same material as the transparent substrate of the front plate. The substrate of the touch sensor is preferably one having a toughness of 2,000 MPa% or more from the viewpoint of suppressing cracks that may occur in the touch sensor. More preferably, the toughness is 2,000 MPa% to 30,000 MPa%. Here, toughness is defined as the area under the curve up to the breaking point in a stress (MPa)-strain (%) curve obtained through a tensile test of a polymer material. EXAMPLES

[0076] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.

[0077] [Moisture permeability] Test materials: Moisture permeability is 70000g / (m 2 The test materials were prepared by laminating the first adhesive layer alone (Example 1, Comparative Examples 1 and 2) or a laminate of a second adhesive layer, a functional layer and the first adhesive layer (Example 2 and Comparative Example 3) onto the surface of a support (layer) having a life of more than 100 days. Moisture permeability measurement method: A water vapor transmission meter (Systech Illinois (UK) "Lyssy80-4000", compliant with JIS K7129-1:2019 (humidity sensor method)) was used to measure the humidity in the 0.07 to 51 cm2 area. 2 Under conditions of a permeation cell temperature of 40°C and a relative humidity of 90% in the high humidity chamber, the measurement start threshold on the low humidity chamber side was set to a relative humidity of 9.7% and the measurement was started. The time required for the relative humidity in the low humidity chamber to change from 9.9% RH to 10.1% RH was measured and the moisture permeability was calculated as water vapor transmission rate.

[0078] [Evaluation of iodine loss] As shown in FIG. 3, the polarizing plate with the adhesive layer was cut into a rectangle of 120 mm (L2) × 60 mm (L1) so that the angle α of the absorption axis T of the polarizer with respect to the long side L2 was 45° when the protective film A side (A side) was placed on the upper side, and the plate was laminated to an alkali-free glass plate (manufactured by Corning, product name "Eagle-XG"), and then left for 168 hours in an environment of a temperature of 65°C and a humidity of 90%RH. Thereafter, a polarizing plate in a cross-Nicol relationship was laminated to the alkali-free glass surface opposite to the tested polarizing plate with the adhesive layer, and the observed image was stored. The optical microscope used was "VHX-500" manufactured by Keyence Corporation. FIG. 4 shows an example of an observation image of the polarizing plate with the adhesive layer observed in this way with an optical microscope. This observation image is an observation image of a polarizing plate with an adhesive layer obtained by Example 1 described later. In Figure 4, when observing along the straight line indicated by the arrow from the edge 50 of the polarizing plate with an adhesive layer inward (the straight line drawn in white perpendicularly from the edge 50), it can be seen that there are iodine-free regions 51 and regions where iodine-free has not occurred (non-iodine-free regions) 52.

[0079] [Measurement of iodine loss by image processing] The image observed under a microscope shown in FIG. 4 is a gray image converted to 256 grayscale levels (0 to 255) using the image analysis software "ImageJ (free software)". The method of converting to 256 grayscale levels (0 to 255) was a method of averaging RGB values. FIG. 5 shows profile data in which the grayscale levels are plotted along the straight line drawn in white for the observed image after conversion to 256 grayscale levels shown in FIG. 4. The midpoint (the middle of the iodine-free gradation) between the iodine-free region 51 and the non-iodine-free region 52 in the grayscale profile in the direction perpendicular to the end 50 of the polarizing plate with an adhesive layer (arrow in FIG. 4) was taken as the iodine-free end of the polarizing plate with an adhesive layer (FIG. 5), and the distance (μm) from the end 50 of the polarizing plate with an adhesive layer to the iodine-free end was measured as the iodine-free distance. The iodine-free distance of the polarizing plate with an adhesive layer is shown in Table 1. The smaller the iodine-free distance, the narrower the iodine-free range and the better the resistance to moisture and heat.

[0080] [Curl measurement] As the protective film, AY-638 manufactured by Fujimori Kogyo Co., Ltd. (comprised of a 15 μm thick adhesive layer on a 38 μm thick polyester film) was prepared. A polarizing plate with a protective film was prepared by laminating a protective film onto the protective film A of the polarizing plate with the adhesive layer. A sample for curl measurement was cut into a rectangle measuring 120 mm x 60 mm so that the absorption axis of the polarizer of the polarizing plate with the protective film was at 45° to the long side, and was left in an environment of 23°C / 55% RH for 15 hours. Thereafter, the separator film was peeled off from the first pressure-sensitive adhesive layer of the curl measurement sample, and the curl measurement was performed. The sample was left in an environment of 23°C / 15% RH for 1 hour, and then the curl measurement was performed again, and the amount of change in the curl value was calculated.

[0081] The curl measurement will be described with reference to FIG. 6. In the curl measurement, a curled polarizing plate sample 21 with an adhesive layer is placed on a reference surface 25 (for example, a flat surface on a desk, etc.) with its convex surface (protective film side) facing down. In FIG. 6, the surface of the sample when it is assumed that there is no curl is shown as a virtual surface 23 represented by a rectangle ABCD. One of the four corners A of the virtual surface 23 is at the position A1 in the curled polarizing plate sample 21 with an adhesive layer, another corner C is at the position C1 in the curled polarizing plate sample 21 with an adhesive layer, and other corners B and D are at the positions B1 and D1 in the curled polarizing plate sample 21, and B1 and B are shown to be in the same position, and D1 and D are shown to be in the same position (that is, B and D of the four corners of the sample correspond to a state where there is no lift). However, in reality, three or all of the four corners of the sample may be lifted. In this manner, for each of the four corners A1, B1, C1, and D1 of the sample, the curl height H from the reference plane 25 is measured. The maximum value of the lift heights of the four corners is determined, and this maximum value is regarded as the curl value of the sample.

[0082] [Single-sided protective polarizing plate] (Preparation of polarizer) A polyvinyl alcohol film having a thickness of 20 μm, a degree of polymerization of 2400, and a degree of saponification of 99% or more was uniaxially stretched to a stretching ratio of 4.1 times on a heated roll and, while maintaining the tension, was immersed for 60 seconds at 28° C. in a dye bath containing 0.05 parts by mass of iodine and 5 parts by mass of potassium iodide per 100 parts by mass of water.

[0083] Next, the film was immersed in boric acid aqueous solution 1 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide per 100 parts by mass of water at 64°C for 110 seconds. Next, the film was immersed in boric acid aqueous solution 2 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide per 100 parts by mass of water at 67°C for 30 seconds. Thereafter, the film was washed with pure water at 10°C and dried to obtain a polarizer. The obtained polarizer had a thickness of 8 μm and a boron content of 4.3 wt%.

[0084] (Preparation of Water-Based Adhesive) 3 parts by mass of carboxyl-modified polyvinyl alcohol (Kuraray Co., Ltd., product name "KL-318") was dissolved in 100 parts by mass of water, and the resulting aqueous solution was mixed with a polyamide epoxy additive (Taoka Chemical Co., Ltd., product name "Sumirez Resin (registered trademark) 650 (30)"), which is a water-soluble epoxy resin. 」 Aqueous solution having a solid content of 30% by weight) was added in an amount of 1.5 parts by mass to prepare a water-based adhesive.

[0085] (Protective film A and release film B) As the protective film A, a film (manufactured by Nippon Paper Industries Co., Ltd., product name "COP25ST-HC") was used, in which a hard coat layer having a thickness of 3 μm was formed on a stretched film made of a cyclic polyolefin resin having a thickness of 25 μm. A triacetyl cellulose film (manufactured by Fujifilm Corporation, "TD80UL") was used as the release film B. The release film had a thickness of 80 μm and a moisture permeability of 502 g / m 2 -It was 24 hours.

[0086] (Preparation of single-sided protective polarizing plate) The prepared polarizer was continuously transported, and the protective film A was continuously unwound from the roll of the protective film A, and the release film B was continuously unwound from the roll of the release film B. A water-based adhesive was injected between the polarizer and the corona-treated protective film A, and pure water was injected between the polarizer and the release film B, and the laminated film was passed through a lamination roll to obtain a laminated film consisting of the protective film A / water-based adhesive / polarizer / pure water / release film B. The laminated film was transported and subjected to a heat treatment at 80°C for 300 seconds in a drying furnace to dry the water-based adhesive and to volatilize and remove the pure water interposed between the polarizer and the release film B, thereby obtaining a single-sided protected polarizing plate with a release film. The release film B was peeled off from the single-sided protected polarizing plate with a release film to obtain a single-sided protected polarizing plate.

[0087] [Preparation of retardation laminate] (Preparation of the first retardation layer) The first retardation layer was a layer that gave a retardation of λ / 4 and was composed of a first liquid crystal layer, which was a layer of a cured nematic liquid crystal compound, an alignment film, and a transparent substrate. The total thickness of the layer of the cured nematic liquid crystal compound and the alignment layer was 2 μm.

[0088] (Preparation of the second retardation layer) As a composition for forming an alignment layer, 10.0 parts by mass of polyethylene glycol di(meth)acrylate (A-600, manufactured by Shin-Nakamura Chemical Co., Ltd.), 10.0 parts by mass of trimethylolpropane triacrylate (A-TMPT, manufactured by Shin-Nakamura Chemical Co., Ltd.), 10.0 parts by mass of 1,6-hexanediol di(meth)acrylate (A-HD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.), and 1.50 parts by mass of Irgacure 907 (Irg-907, manufactured by BASF) as a photopolymerization initiator were dissolved in 70.0 parts by mass of methyl ethyl ketone solvent to prepare a coating liquid for forming an alignment layer.

[0089] A long cyclic polyolefin resin (COP) film (manufactured by Zeon Corporation) having a thickness of 20 μm was prepared as a substrate film, and the coating liquid for forming an alignment layer was applied to one side of the substrate film using a bar coater.

[0090] After the coating layer was heat-treated at 80°C for 60 seconds, it was exposed to ultraviolet light (UVB) at 220 mJ / cm 2 The composition for forming the alignment layer was polymerized and cured by irradiation to form an alignment layer having a thickness of 2.3 μm on the substrate film.

[0091] As a composition for forming a retardation layer, 20.0 parts by mass of a photopolymerizable nematic liquid crystal compound (RMM28B, manufactured by Merck) and 1.0 part by mass of Irgacure 907 (Irg-907, manufactured by BASF) as a photopolymerization initiator were dissolved in 80.0 parts by mass of propylene glycol monomethyl ether acetate solvent to prepare a coating liquid for forming a retardation layer.

[0092] A coating solution for forming a retardation layer was applied onto the previously obtained alignment layer, and the coating layer was subjected to a heat treatment at a temperature of 80° C. for 60 seconds. Then, ultraviolet rays (UVB) were applied at 220 mJ / cm 2 The retardation layer-forming composition was polymerized and cured by irradiation to form a 0.7 μm-thick second liquid crystal cured layer on the alignment layer. In this way, a 3 μm-thick second retardation layer consisting of the alignment layer and the second liquid crystal cured layer was obtained on the substrate film.

[0093] (Preparation of Retardation Laminate) The first retardation layer and the second retardation layer were bonded together with an ultraviolet-curing adhesive (thickness 1 μm) so that the liquid crystal layer surface (the surface opposite to the substrate film) of each layer was bonded. Then, the ultraviolet-curing adhesive was cured by irradiation with ultraviolet light to produce a retardation laminate including two retardation layers, the first retardation layer and the second retardation layer. The thickness of the retardation laminate including the first retardation layer, the ultraviolet-curing adhesive layer, and the second retardation layer was 6 μm.

[0094] (1st adhesive layer) Adhesive layer (1): moisture permeability 930g / (m 2 A 25 μm thick film was prepared. Adhesive layer (2): moisture permeability 2000g / (m 2 A 25 μm thick film was prepared. Adhesive layer (3): moisture permeability 160g / (m 2A 25 μm thick film was prepared.

[0095] (Second adhesive layer) Moisture permeability 4000g / (m 2 A 5-μm thick film was prepared.

[0096] <Example 1> An adhesive layer (1) was attached to the polarizer side of the produced single-sided protected polarizing plate, and the separator was peeled off to obtain a polarizing plate with an adhesive layer of Example 1. The polarizing plate with an adhesive layer of Example 1 had a structure as shown in Figure 1. The results are shown in Table 1. The moisture permeability was measured for the adhesive layer alone.

[0097] <Comparative Example 1> A polarizing plate with a pressure-sensitive adhesive layer was produced in the same manner as in Example 1, except that the pressure-sensitive adhesive layer (2) was used instead of the pressure-sensitive adhesive layer (1) in Example 1. The results are shown in Table 1. The moisture permeability was measured for the pressure-sensitive adhesive layer alone.

[0098] <Comparative Example 2> A polarizing plate with a pressure-sensitive adhesive layer was produced in the same manner as in Example 1, except that the pressure-sensitive adhesive layer (3) was used instead of the pressure-sensitive adhesive layer (1) in Example 1. The results are shown in Table 1. The moisture permeability was measured for the pressure-sensitive adhesive layer alone.

[0099] [Table 1]

[0100] <Example 2> A second adhesive layer was attached to the polarizer side of the prepared single-sided protected polarizing plate, and the separator was peeled off. The surface of the second adhesive layer from which the separator was peeled off was attached to the first liquid crystal cured layer side of the retardation laminate from which the transparent substrate had been removed, and the substrate film of the second retardation layer was peeled off. An adhesive layer (1) was attached to the surface from which the substrate film had been peeled off. The polarizing plate with the adhesive layer of Example 2 had a configuration as shown in FIG. 2. The results are shown in Table 2. The moisture permeability was measured for a laminate of the second adhesive layer, the functional layer, and the first adhesive layer.

[0101] <Comparative Example 3> The same procedure as in Example 2 was repeated except that the adhesive layer (3) was used instead of the adhesive layer (1). 2 A polarizing plate with a pressure-sensitive adhesive layer was produced in the same manner as in Example 1. The results are shown in Table 2. The moisture permeability was measured for a laminate of the pressure-sensitive adhesive layer and the functional layer attached to each other.

[0102] [Table 2] [Explanation of symbols]

[0103] 11 protective film, 12 adhesive layer, 10 polarizer, 13 first adhesive layer, 14 second adhesive layer, 15 functional layer, 21 curled polarizing plate sample, 23 virtual surface, 25 reference surface, 50 edge of polarizing plate with adhesive layer, 51 iodine-free area, 52 non-iodine-free area, 100, 200 polarizing plate with adhesive layer, T transmission axis direction, A, B, C, D corners of virtual surface, A1, B1, C1, D1 corners of sample, H curl height

Claims

1. A polarizing plate with a pressure-sensitive adhesive layer in which a protective film is disposed on only one side of a polarizer, the polarizer, the protective film disposed on one side of the polarizer via an adhesive layer, and a first pressure-sensitive adhesive layer disposed directly on the other side of the polarizer; A first pressure-sensitive adhesive layer is provided on the other side of the polarizer, the polarizer is a hydrophilic polymer film having iodine adsorbed thereon; The first pressure-sensitive adhesive layer has a moisture permeability of 700 g / (m 2 ・day) or more 1500g / (m 2 ・day) or less, A polarizing plate with a pressure-sensitive adhesive layer, wherein the first pressure-sensitive adhesive layer has a thickness of 10 μm or more.

2. The polarizing plate with a pressure-sensitive adhesive layer according to claim 1 , wherein the first pressure-sensitive adhesive layer is a layer made of a pressure-sensitive adhesive containing a (meth)acrylic resin.

3. The polarizing plate with a pressure-sensitive adhesive layer according to claim 1 , wherein the protective film is a film made of a cyclic polyolefin resin.

4. A laminate for a flexible image display device, comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of claims 1 to 3, and a front panel or a touch sensor.

5. An image display device comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of claims 1 to 3.

6. A polarizing plate with a pressure-sensitive adhesive layer in which a protective film is disposed on only one side of a polarizer, a polarizer; and the protective film disposed on one side of the polarizer via an adhesive layer, and a second pressure-sensitive adhesive layer, a functional layer, and a first pressure-sensitive adhesive layer, in this order, on the other side of the polarizer; the second adhesive layer is disposed directly on the polarizer; The functional layer is a single layer of a liquid crystal cured layer alone, or a multilayer composed of a liquid crystal cured layer and one or more layers selected from the group consisting of a liquid crystal cured layer, an alignment layer, and an attachment layer, the polarizer is a hydrophilic polymer film having iodine adsorbed thereon; The moisture permeability of a laminate composed of the second pressure-sensitive adhesive layer, the functional layer, and the first pressure-sensitive adhesive layer at a temperature of 40° C. and a relative humidity of 90% R.H. is 180 g / (m 2 ・day) or more 1500g / (m 2 .day) or less.

7. The polarizing plate with a pressure-sensitive adhesive layer according to claim 6 , wherein the protective film is a film made of a cyclic polyolefin resin.

8. The pressure-sensitive adhesive layer-attached polarizing plate according to claim 6 , wherein the functional layer includes a first liquid crystal cured layer and a second liquid crystal cured layer.

9. A laminate for a flexible image display device, comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of claims 6 to 8, and a front panel or a touch sensor.

10. An image display device comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of claims 6 to 8.

Citation Information

Patent Citations

  • Adhesion type polarizing plate and image display device

    JP2012247574A

  • Polarizing plate

    JP2016066074A

  • Polarizing film with adhesive layer, optical member, and image display device

    JP2017058519A

  • Circular polarizing plate and flexible image display device using the same

    JP2017111432A

  • Optical film for organic el display devices, polarizing film for organic el display devices, polarizing film with adhesive layer for organic el display devices, and organic el display device

    JP2017203835A